(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Squamous cell carcinoma (SCC) is the most common Sinonasal neoplasm and accounts for 50-60% of all Sinonasal malignancies. This is an aggressive malignancy that presents itself insidiously and is generally advanced when diagnosed; but distant metastases are rare. We reported a case of a patient with SCC of Sinonasal tract with an unusual pattern of bone metastases. Case report: A 45-year-old male with epistaxis and palatine mass was diagnosed with undifferentiated non-keratinizing squamous cell carcinoma of Sinonasal tract, accompanied by swelling and joint pain. X-ray of right wrist joint suggested primary bone tumor with the differentials of aneurysmal bone cyst or fibrous dysplasia. Whole body 99mTc-MDP bone scintigraphy demonstrated increased radiotracer uptake bilaterally in various joints, including shoulder, elbow, wrist, metacarpal, knee, ankle, and metatarsal joints. Regional SPECT-CT revealed lytic lesions with irregular cortical destruction in various body parts, including scapulae, clavicle, humeri, radius, ulna, metacarpal bones, femurs, tibia, fibula, and talus, suggesting metastases. Periosteal reactions in both ulnas and a pathological fracture in the right ulna were detected, and a biopsy confirmed the presence of metastatic disease. Conclusion: Bone scintigraphy with regional SPECT-CT plays a useful role in detecting bone metastases in Sinonasal squamous cell carcinoma, thus helps in staging as well as management of the patient. Bangladesh J. Nuclear Med. 27(2): 276-278, 2024